2001
DOI: 10.1016/s0002-9440(10)61730-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peroxisome Proliferator-Activated Receptor γ and Its Ligands in Non-Neoplastic and Neoplastic Human Urothelial Cells

Abstract: Peroxisome proliferator-activated receptor gamma (PPARgamma) is a member of the nuclear receptor superfamily of ligand-activated transcription factors and is expressed in several types of tissue. Although PPARgamma reportedly is expressed in normal urothelium, its function is unknown. We examined the expression of PPARgamma in normal urothelium and bladder cancer in an attempt to assess its functional role. Immunohistochemical staining revealed normal urothelium to express PPARgamma uniformly. All low-grade ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
75
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 23 publications
8
75
1
2
Order By: Relevance
“…Europe and North America have the highest incidence of bladder cancer, with a higher incidence in those with diabetes [1,2]. Peroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear transcription factor which, in addition to being expressed in normal urothelium, is overexpressed in bladder tumours [3,4]. Pioglitazone and rosiglitazone are thiazolidinediones (TZDs) which act as PPARγ agonists and are used in the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Europe and North America have the highest incidence of bladder cancer, with a higher incidence in those with diabetes [1,2]. Peroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear transcription factor which, in addition to being expressed in normal urothelium, is overexpressed in bladder tumours [3,4]. Pioglitazone and rosiglitazone are thiazolidinediones (TZDs) which act as PPARγ agonists and are used in the treatment of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…PPARg is highly expressed in tumor samples from different sites, and, in one study, wild-type PPARg mRNA was observed in multiple tumors and in 34 hematopoietic cancer cell lines as well as several lung (10), colon (10), duodenal (1), prostate (5), breast (4), and glioblastoma (2) cell lines (13). PPARg has also been detected in bladder tumors and bladder cancer cell lines (14)(15)(16)(17) and is expressed in the epithelium of the bladder but not surrounding smooth muscle or interstitium (15). PPARg is an excellent target for cancer chemotherapy not only because of its elevated expression in tumors but also because PPARg activation results in decreased cell proliferation, decreased G 0 -G 1 to S phase progression, increased differentiation, and apoptosis (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in keeping with the suggestion that PPARg acts as a tumor suppressor gene (Nakajima et al, 2001;Smith et al, 2001;Koeffler, 2003). Mechanisms of PPARg-mediated antitumor activity by Tzds demonstrated experimentally include induction of cellular differentiation (Elstner et al, 1998;Guan et al, 1999;Kitamura et al, 1999;Chang and Szabo, 2002;Kawa et al, 2002), promotion of cell cycle arrest (Brockman et al, 1998;Kitamura et al, 1999;Motomura et al, 2000;Itami et al, 2001;Koga et al, 2001;Nakashiro et al, 2001;Takashima et al, 2001;Yin et al, 2001;Kawa et al, 2002;Hong et al, 2004;Rumi et al, 2004;Chen and Harrison, 2005), antiangiogenic effects (reviewed in Alarcon de la Lastra et al, 2004) and induction of apoptosis (Elstner et al, 1998;Kubota et al, 1998;Chang and Szabo, 2000;Tsubouchi et al, 2000;Eibl et al, 2001;Takashima et al, 2001;Yang and Frucht, 2001;Lovekamp-Swan and Chaffin, 2005;Yuan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%